THE DISTINCTION BETWEEN TEAMS RANKED THIRD AND FOURTH IN THE SUPER LEAGUE VOLLYEBALL OF KOSOVO - Bahri Gjinovci; Valon Nikqi; Florian Miftari (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2014)
Introduction: When it is about elite male volleyball players, it is always meant about players that possess such anthropometric parameters which correspond with volleyball game. In this research we are deal with two teams of the super league of Kosovo in volleyball. The goal of this study is to verify the differences between the two teams in volleyball in some anthropometric characteristics, basic motor skills and situational tests. Methods: For the realization of this research, there were included 12 volleyball player from the team KV "Granit com" and 12 from the team KV "Te Luzha". There are applied 4 anthropometric variables (body weight, body height, arm length, forearm length), 5 basic motor variables (long jump from place, high jump from the place taping hand, taping feet, jogging with 20 meters with a fast start), and 7 situational tests (pass the ball with the fingers on target vertical expulsion of the ball with the forearm ("hammer") in vertical target, passing the ball with the fingers in a horizontal target, the expulsion of the ball with the forearm ("hammer") in horizontal target, pass the ball with fingers to jump in the horizontal target, tennis service in horizontal target, the target service with the horizontal jump. For processing the obtained results from the measurements and proving the difference between the teams in anthrop motored parameters, was used the discriminatory analysis using the t-test for independent variables. Results: The results obtained show that the players of the two volleyball teams of the Super League in of Kosova, involved in the research do not distinguish between them in anthropometric characteristics (p> 0:05). The team KV "Granit Com" has had better results in some motor variables of the explosive force and the one of long jump from the place(P <0:05) and running 20 meters from a fast start (p <0:01). Situational tests are not a statistically significant difference observed between the two teams. Discussion: In order to verify the statistical significance through the t-test, the value of t-test should be established, which for significant level p<0.05 is T>1.97 above 20 entities. The results show that statistically valid changes with valid significant tests are present in anthropometric and movement space. Table nr.15 presents the results of two teams "Graniti Com" and "Te Luzha". In this case, the statistical valid changes are presented in three tests: high jump, 20 meters speed run and accuracy of the service in jumping. References: Liba MR, Stauff MR (1963). Research Quarterly, 35, 59-63. Strahova A (1972). Kineziologija, 1, 19-72. Nikqi V. (2008). Differences of some anthopmetric and motor characteristics as well as several situatinal testes among Kosovo Superlague Volleyball players, 35-64. Strahonja A, Jankovic V, Shnajder V (1982), Kineziologija, 11, 46-51.